PERANCANGAN KOLEKSI BUSANA SIAP PAKAI DELUXE UNTUK WANITA DENGAN INSPIRASI SIMBOL DAN WARNA SUKU ZULU DI AFRIKA - Tia Erliawati; Dewi Isma Aryani; Indra Jati Tan (Jurusan Seni Rupa ISBI Bandung, 2018)
Africa has a number of tribes and cultures, among other is the Zulu tribe that uses Isi-Zulu language, symbols and colors as means of communication. It has inspired an extravagant ready-to-wear collection entitled “Isiko se-Zulu”. For Zulu women, fashion style depends on their marital status: maiden or not married yet, engaged and married. In the collection, Zulu symbols, colors, ethnic motifs and basic silhouette are made more modern and applied to clothes by using digital printing techniques and enriched with beadwork, embroidery, and tassel.Keywords: Ethnic, Beadwork, Symbol, Zulu Tribe ________________________________________________________________ Afrika memiliki berbagai suku dan budaya, salah satunya adalah suku Zulu yang menggunakan bahasa Isi-Zulu, simbol dan warna sebagai media komunikasi. Hal ini menjadi inspirasi koleksi pakaian siap pakai yang mewah berjudul “Isiko se-Zulu”. Gaya busana wanita Zulu dipengaruhi statusnya: masih gadis atau tidak menikah, bertunangan, atau menikah. Dalam koleksi pakaian ini, symbol, warna, motif etnis dan siluet dasar Zulu dibuat lebih modern dan diterapkan pada pakaian menggunakan teknik cetak digital, dengan detail manik-manik, bordir, dan rumbai.Kata Kunci: Etnis, Manik-manik, Simbol, Suku Zulu